Convenient synthesis and crystal structure of a monomeric zinc hydride complex with a three-coordinate metal center - Spielmann, Jan; Piesik, Dirk; Wittkamp, Bernd; Jansen, Georg; Harder, Sjoerd (Chemical Communications, 2009)
Convenient syntheses for a β-diketiminate zinc hydride complex, that crystallizes as a monomer with a three-coordinate Zn atom, have been developed. © 2009 The Royal Society of Chemistry.